Kandungan Xantofil Daun Lamtoro (Leucaena leucocephala) Hasil Detoksikasi Mimosin Secara Fisik dan Kimia - E B Laconi; T Widiyastuti (Media Peternakan, 2010)
Leucaena (Leucena leucocephala) is a feed source which has high protein and carotenoid, but its utilization as feed was limited by the presence of mimosine (β-N-(3-Hydroxy-4 pyridone)-α amino propenoic acid as a toxin. Experiment was carried out using completely randomized design with 4 detoxification treatments and 5 replications. Detoxification treatments of leucaena leaf consisted of (1) non treated leucaena leaf, (2) steamed heating at 70 oC for 15 minutes, (3)  dry heating at 70 oC for 12 h, (4) soaking with fresh water for 12 h, (5) spray with NaOH 5%, incubated  for 12 h. Variables measured were mimosine and xanthophylls contents. Data were analyzed using analysis of variance and duncan multiple range test was further done to test the significant differences between means. The results showed that soaking leucaena leaf with fresh water for 12 h gave the highest reduction for both mimosine and xanthophylls contents and steamed heating at 70oC for 15 minutes had the highest xanthophylls content post detoxification. It was concluded that steamed heating at 70oC for 15 minutes was the best detoxification methods for mimosine in leucaena leaf.   Key words:  mimosine, Leucaena leucocephala, physical and chemical detoxification